IMC : an integrated marketing communications exercise - Jakacki, Bernard C. (Cincinnati OH : South-Western College, 2001)
Introduction. Briefing by the client: "the factory tour". Competitve advertising and promotion. First assignment: assessing communications. Developing a creative strategy. Second assignment. TV and print media basics...
Keywords: Tourism; Advertising; Tourist trade; Advertising; Tourist trade -- Marketing; Communication in marketing; Public relations